Additive Effect of Neutralizing Antibody and Antiviral Drug Treatment in Preventing Virus Escape and Persistence - Seiler, Peter (American Society for Microbiology, 2000)
Poorly cytopathic or noncytopathic viruses can escape immune surveillance and establish a chronic infection. Here we exploited the strategy of combining antiviral drug treatment with the induction of a neutralizing antibody response to avoid the appearance of neutralization-resistant virus variants. Despite the fact that H25 immunoglobulin transgenic mice infected with lymphocytic choriomeningitis virus mounted an early neutralizing antibody response, the virus escaped from neutralization and persisted. After ribavirin treatment of H25 transgenic mice, the appearance of neutralization-resistant virus was prevented and virus was cleared. Thus, the combination of virus-neutralizing antibodies and chemotherapy efficiently controlled the infection, whereas each defense line alone did not. Similar additive effects may be unexpectedly efficient and beneficial in humans after infections with persistent viruses such as hepatitis C virus and hepatitis B virus and possibly human immunodeficiency virus.